1986
DOI: 10.1002/pros.2990080112
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological observations in the canine prostate treated by local microwave hyperthermia

Abstract: A large series of repeated experiments were performed applying localized microwave hyperthermia to the prostate in dogs using a new water-cooled skirt-type antenna [1], operating at 915 MHz, as part of a new hyperthermia apparatus being developed for the treatment of the prostate in humans. The prostate gland of 20 male dogs was heated repeatedly under general anesthesia, at temperatures between 40 degrees C and 47 degrees C, and for different lengths of time up to 10 h. The prostate and other tissues were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…No atrophic change of glandular epithelial cells in the canine prostate was observed after hyperthermia using microwaves (Leib et al 1986). The cause of the atrophy in the present study is unclear, although it has been reported that the mitochondria are the primary target in the cellular damage induced by laser hyperthermia while the activation of lysosomes is the primary target in other hyperthermia technique (Overgaard 1976;Tsunekawa 1990).…”
Section: Histological Changes After Tubal-h In Dog's Prostates 43mentioning
confidence: 98%
See 1 more Smart Citation
“…No atrophic change of glandular epithelial cells in the canine prostate was observed after hyperthermia using microwaves (Leib et al 1986). The cause of the atrophy in the present study is unclear, although it has been reported that the mitochondria are the primary target in the cellular damage induced by laser hyperthermia while the activation of lysosomes is the primary target in other hyperthermia technique (Overgaard 1976;Tsunekawa 1990).…”
Section: Histological Changes After Tubal-h In Dog's Prostates 43mentioning
confidence: 98%
“…The histological damage in hyperthermia for the normal and hyperplastic canine prostate has been reported to be minimal or limited only to invasion of inflammatory cells in the stroma (Leib et al 1986). The application of hyperthermia using low-power Nd : YAG laser for malignant tumors has been reported (Huang et al 1991).…”
Section: Histological Changes After Tubal-h In Dog's Prostates 43mentioning
confidence: 99%
“…The effects of hyperthermia on hyperplasie cells are not well-known. Leib [2] found that 1 h of hyperther mia on a dog's prostate caused interstitial infiltration of mononuclear cells and infiltration of lymphocytes in the gland tissue without leading to necrosis. Echographie studies did not reveal a significant decrease in prostatic volume with the means that were available for measure ment purposes, but nevertheless the rectal examination performed after treatment showed subjectively a more flexible and less sclerotic gland, which seemed to im prove urine flow and urinary symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Servadio, Leib and Lev [1,2,4,6,8,10] developed a system, for the first time in Israel, using microwaves to heat the prostate gland through the rectum to 42-44 ° C with a Biodan Prosta thermer. Subsequently, Lindner [3,6,10], at the Wolfson Medical Centre, and Braf [10], at the Ichilov Medi cal Centre in Israel, developed study protocols for the treatment of benign prostate hypertrophy and prostatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, second-generation devices with trans urethral antennae delivering intraprostatic temperatures in excess of 45 °C yielding an objective tissue response, namely coagulation necrosis and fibrosis [17][18][19], are being evaluated in several institutions [7][8][9][10]20,21].…”
Section: Methodsmentioning
confidence: 99%